Dictionary of international investment and finance terms - Clark, John Owen Edward (Canterbury, Kent, U.K. : Financial World, 2001)
It provides access to the terms of trade finance for students and professionals in the growing world of international trade and its interaction with banking and the stock exchange.
sju 21/03/2019
Ref.
Keywords: Investments; International finance; Finance